PENGARUH AIRLINDI TERHADAP AIRTANAH DI SEKITAR TEMPAT PEMBUANGAN AKHIR SAMPAH AIR DINGIN KOTA PADANG - Rahmi Novia Putri (Universitas Tamansiswa Padang, 2019)
The purpose of this research are analyze the quality of leachate and groundwater around the landfill, and analyze the effect of landfill on groundwater quality around the landfill. The method used in the research was a survey and laboratory testing. Determination of groundwater samples based on the direction of groundwater flow and using purposive sampling technique. The quality of the leachate and groundwater analyzed descriptively that compared with the Regulation of the Minister of the Republic of Indonesia Number 5 of 2004 regarding Standard Waste Unassigned, while for groundwater compared to the Regulation of the Minister of Health of the Republic of Indonesia No. 491 / Menkes / Per / IV / 2010 / About Terms Drinking Water Quality. The results showed the quality of the leachate in some parameters exceed the quality standard that Ammonia and Total Coliform. While the parameters of groundwater that does not comply with quality standards, namely pH, Iron, Ammonia, Total Coliform. Air Dingin Landfill influence on groundwater quality around the landfill is in the direction of groundwater flow, distance and the location of the well that is lower that the landfill.